New challenges for industrial policy - Wim Naudé (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
This paper calls for a fresh look at industrial policies in the light of recent trends and developments in the global economy. In particular, five new challenges and their implications for industrial policies are discussed. These have been neglected in the debate on industrial policy and include (i) the increasing globalization of the world economy, most pertinently the rise of global production sharing, (ii) the recent crises in food, fuel and financial markets, (iii) climate change, (iv) the rise of China and India, and (v) the rise of the 'entrepreneurial economy'. Directions for further research are outlined. This paper is a follow-up to the earlier WIDER Working Paper entitled 'Industrial Policy: Old and New Issues'.
Keywords: O14; L50; L52; O25; L60; L16; L26; F13; H87; 330; industrial policy; structural transformation; development; financial crisis; climate change